Factors affecting job satisfaction of female employees of private commercial banks in Bangladesh: an empirical investigation - Mohammad Saif, Abu Naser; Uddin, Md. Bashir; Haque, A. K. M. Ahasanul; Rahman, Md. Mizanur; Al Mamun, Mohammad Abdullah (Scientific & Academic Publishing, 2016)
Job satisfaction is the most extensively discussed issue in Organizational Behavior, Human Resource Management, and Organizational Management. This study aims at indentifying some important factors that affect job satisfaction of female employees of private commercial banks in Bangladesh. A highly structured questionnaire was prepared to collect primary data from 110 female employees working at private commercial banks in Bangladesh. Several statistical tools and techniques, i.e. Descriptive Analysis, ANOVA, Pearson Correlation, and Multiple Regression have been used to determine authentic findings and draw a significant conclusion. The findings of the study reveal significant factors, i.e. job security, participation in decision making, available leave facilities, attitude of top management, salary increment, specific time for family, promotion opportunity, flexible working hour etc. affect job satisfaction of female employees of private commercial banks. Hence, the authority should address those key factors properly for the development of private commercial banking sector in Bangladesh.